If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 1 = 20x Reorder the terms: 1 + 4x = 20x Solving 1 + 4x = 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. 1 + 4x + -20x = 20x + -20x Combine like terms: 4x + -20x = -16x 1 + -16x = 20x + -20x Combine like terms: 20x + -20x = 0 1 + -16x = 0 Add '-1' to each side of the equation. 1 + -1 + -16x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -16x = 0 + -1 -16x = 0 + -1 Combine like terms: 0 + -1 = -1 -16x = -1 Divide each side by '-16'. x = 0.0625 Simplifying x = 0.0625
| 3xz-3xy=0 | | 10squared=5x-(5x-x)(5x-x) | | 0.05xa=5 | | 8d-4=12-14 | | 5sinx-12cosx-9=0 | | 7(p-8)=8p+35 | | (-1)a=-a | | R=H+4*20 | | 10+2x^3=7 | | 4*4x+7-5x=8+(-5)(5x-6x)+23 | | 3x+3(-2x)=x-3 | | 3(m+5)= | | 7(2x-1)=4x+3 | | g(x)=-3x^2+30x-77 | | 114=19y | | p^2(p^2-4)=3p^2+-8 | | 3*4x=35+5x | | 9w=5670 | | p^2(p^2-4)=3p^2-8 | | -16x^2+105x-34= | | 2*4x+4=28 | | -16x^2-105x-34= | | (5x-15)(2-x)=0 | | 10-4x=x-16-3x | | 9x+3=5x+3 | | 12=3-5k | | 9x-6x+3=7x-2x | | 2(3-x)=3(x+15) | | 21=5+33t-16t^2 | | 5x-9=2x+14 | | 800=.4x | | x^2+5y^2-4xy+6y+10=1 |